2021
DOI: 10.1007/s00421-020-04580-6
|View full text |Cite
|
Sign up to set email alerts
|

Can exercise training enhance the repeated remote ischaemic preconditioning stimulus on peripheral and cerebrovascular function in high-risk individuals?

Abstract: Background Repeated exposure to remote ischaemic preconditioning (rIPC; short bouts of non-lethal ischaemia) enhances peripheral vascular function within 1 week; whereas, longer periods of rIPC (~ 1 year) may improve cerebral perfusion. Increasing the ‘dose’ of rIPC may lead to superior effects. Given the similarities between exercise and rIPC, we examined whether adding exercise to the rIPC stimulus leads to greater adaptation in systemic vascular function. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…According to the statistical data [ 12 ], the incidence and mortality of lung cancer in males rank the first among malignant tumors, and its incidence in female ranks the third. As most patients have already suffered from medium and advanced lung cancer when they are diagnosed, they have such severe symptoms as cough, expectoration, fever, emaciation, cachexia, and dyspnea, which seriously threaten their daily activities and quality of life [ 13 15 ]. At present, the patients with medium and advanced lung cancer are mainly treated with radiochemotherapy, which can improve the patients' condition and increase their survival time.…”
Section: Discussionmentioning
confidence: 99%
“…According to the statistical data [ 12 ], the incidence and mortality of lung cancer in males rank the first among malignant tumors, and its incidence in female ranks the third. As most patients have already suffered from medium and advanced lung cancer when they are diagnosed, they have such severe symptoms as cough, expectoration, fever, emaciation, cachexia, and dyspnea, which seriously threaten their daily activities and quality of life [ 13 15 ]. At present, the patients with medium and advanced lung cancer are mainly treated with radiochemotherapy, which can improve the patients' condition and increase their survival time.…”
Section: Discussionmentioning
confidence: 99%
“…Outside the context of clinical studies, the role of repeated RIPC in preventative medicine to reduce CVD progression is also warranted. A recent study indicated that 8 weeks of combined exercise and RIPC did not improve vascular function more than RIPC alone (Maxwell et al., 2021); however, the additive or overlapping effects of exercise and RIPC required further characterization. Additionally, RIPC may have neuromuscular and neuroprotective effects and thus could have application to exercise performance or with maintaining cognitive function.…”
Section: Introductionmentioning
confidence: 99%